Mechanistic modeling of size exclusion chromatography-assisted in vitro refolding of the recombinant biosimilar teriparatide (PTH-34) - Ughade, Santosh; Rana, Sunil; Nadeem, Mohd; Kumthekar, Rupali; Mahajani, Sanjay; Bhambure, Rahul (ACS Omega, 2024)
In vitro protein refolding is one of the critical unit operations in manufacturing recombinant peptides expressed using Escherichia coli as host cells. This study is focused on designing size exclusion chromatography-assisted in vitro refolding process for biosimilar recombinant parathyroid hormone. Inclusion bodies (IBs) of recombinant parathyroid hormone were solubilized at higher pH, and in vitro refolding was performed using size exclusion chromatography. In the first part of the investigation, DoE-based empirical optimization was performed to achieve a higher refolding yield for a biosimilar recombinant parathyroid hormone. The effect of solubilized inclusion body (IB) feed volume, concentration of IBs, and residence time on in vitro refolding of recombinant teriparatide was studied using the Box-Behnken design. Size exclusion chromatography (SEC)-assisted in vitro refolding was performed at 8 C-degrees at pH 10.5 by using 20 mM Tris buffer. The maximum refolding yield of 98.12% was achieved at feed volume (12.5% of CV) and 20 mg/mL inclusion body (IB) concentration with a residence time of 50 min and a purity of 66.1% based on densitometric analysis using SDS-PAGE. In the latter part of the investigation, the general rate mechanistic model framework for size exclusion chromatography was developed and validated with the experimental results. The developed model helped in the accurate prediction of the elution volumes and product yield. The developed model also helps to predict the elution performance of a scalable column a priori. Post in vitro refolding, the formation of the native peptide structure was examined using various orthogonal analytical tools to study the protein's primary, secondary, and tertiary structures. The developed hybrid process development approach is a valuable tool toachieve high-yield, scalable refolding conditions for recombinant proteins without disulfide bonds.

Feasibility study of reactive chromatography for the synthesis of 2-ethoxyethyl acetate using the amberlyst-15 catalyst - Gore, Jayram I.; Nadeem, Mohd; Mahajani, Sanjay M.; Mali, Nilesh A. (Industrial & Engineering Chemistry Research, 2025)
Reactive chromatography is a promising process intensification technology that combines reaction and separation in a single piece of equipment. In this study, the reaction kinetics and adsorption behavior of esterification of 2-ethoxyethanol (EC) with acetic acid (AcOH) using Amberlyst-15 as a catalyst are studied using batch reactions and reactive chromatography. Batch reactions are performed to study the kinetic behavior, and an appropriate kinetic model is proposed. To evaluate adsorption parameters, nonreactive separation experiments are performed in a fixed bed chromatographic reactor (FBCR), and results are compared with model predictions. Further, the MATLAB simulations are performed for reactive separation using kinetics and adsorption data, and results are validated by the experiments. Experimentally obtained breakthrough profiles of FBCR for reaction and desorption reveal the applicability of reactive chromatography for the synthesis of ethyl cellosolve.